Images of The World in Brazil: International News in Two Daily Newspapers in 2006 - Moreira, Sônia Virgínia (Brazilian journalism research, 2007)
The dependence of Brazilian press on the international news agencies suggests that, despite the evolution of technology which now facilitates the access to information, there has been no advance in the basic issues that motivated the debate on the equilibrium necessary in the worldwide circulation of information. The analysis of the journalistic content of the international news published in a specifc week of 2006 in the newspapers Jornal do Brasil, in Rio de Janeiro, and O Estado de S. Paulo, in Sao Paulo, despite the technological transformation in the last decades, shows that Brazil remains a peripheral nation, and the Brazilian foreign correspondents today play much more the role of war correspondents, with their professional movements generally guided by the degree of importance of and by proximity (not geographic, but that of varied interests) to the conficts that break out in diferent points of the planet.